Carbon Dioxide and Ocean Acidification - Peter Stallinga (European Scientific Journal, ESJ, 2018)
One of the results of Anthropogenic Global Warming is the acidification of the oceans which threatens wildlife on this planet. In this work it will be shown what will be the effect of carbon dioxide injected into the atmosphere, doubling the total amount from 350 ppm to 700 ppm. Principally the effect on carbonate ions CO32-. It is based on textbook chemical principles worked out by numerically solving the resulting non-linear equations by the bisection method. The results are the following: In a pure-water environment the effect is that carbonate ion concentration remains unaltered (i.e., no harm to coral reefs). In a constant-pH environment the carbonate ion concentration grows linearly with CO2 in the atmosphere (i.e., good for coral reefs). When lowering the pH by other means than CO2, the carbonate ion concentration drops linearly (i.e., bad for coral reefs). In some specific cases can raising the CO2 in the atmosphere slightly reduce carbonate ions in the oceans.